PP.17.04: COMPARISON OF AN IN-PHARMACY AUTOMATED BLOOD PRESSURE KIOSK TO DAYTIME AMBULATORY BLOOD PRESSURE IN HYPERTENSIVE SUBJECTS. (June 2015) - Padwal, R.; Townsend, R.; Trudeau, L.; Hamilton, P.; Gelfer, M.
Abstract : Objective: Millions of readings are taken from in-pharmacy kiosks daily in North America but information on the accuracy of these kiosks is limited. We sought to compare serial readings from an in-pharmacy automated BP kiosk to mean daytime ambulatory BP. Design and method: 100 community-dwelling adults with hypertension underwent: a. three baseline automated office readings; b. three in-pharmacy kiosk readings on each of four visits (12 total) using the PharmaSmart PS-2000 kiosk; and c. 24-hour ambulatory BP monitoring between in-pharmacy visits two and three. The primary analysis compared the in-pharmacy device to daytime ambulatory readings. A secondary analysis compared the baseline automated office device to daytime ambulatory blood pressure. Paired t-tests, Bland-Altman plots and Pearson's correlation coefficients were used for analysis. Results: Mean BPs were 137.8 ± 13.7/81.9 ± 12.2 mmHg for in-pharmacy and 135.5 ± 11.7/79.7 ± 10.0 mmHg for daytime ambulatory (difference of 2.3 ± 9.5/2.2 ± 6.9 mmHg [p = <0.05]). Bland-Altman plots depicted a high degree of blood pressure variability but did not show clinically important systematic BP differences. With ambulatory BP as the reference standard, in-pharmacy device results were similar to automated office. Correlation with daytime ambulatory BP was 0.73 for SBP and 0.83 for DBP (p < 0.0001 for both) for the in-pharmacy device and, 0.58 for SBP and 0.66 for DBP (p < 0.0001 for both) for the automated device. Conclusions: The PharmaSmart PS-2000 closely approximated mean daytime ambulatory BP, supporting the use of serial readings from this device in the assessment of BP.